Vascularização arterial e venosa do linfonodo poplíteo em cães - Villar, Krina de Senna [UNESP]; Souza, Wilson Machado de [UNESP] (My University, 2009)
Poplíteo lympho nodes in the dogs is placed, to the right and the left in popliteo an appointed space fossa, in distal part of the muscles femoral biceps, laterally and semi-tendinous, medially, projecting in the height of the face volume of the joint to femoro tibial e femoro patellar (joint of the knee). In this study twenty and five dogs, males and females adult, originating the Araçatuba municipal kennel had been used whose captures had been effected by the animal sanitary defense of this city. The arterial vessels destined to this structure always derive, of both the sides, the femoral artery distal volume and vary of 10 the 1, more frequently of 2 (7 times, 28%) to the right and of 6 the 2, equally more frequently of 2 (8 times, 32%). So soon as one has still to right 5 and 6 branches (3 times, 12%), 1, 7 and 10 (1 time, 4%). Relatively to the veins derived from this lympho nodes, always converges to the lateral safena vein, these vessels oscillates between 9 and 2, more frequently of 3 (6 times, 24%), to the right and of 12 the 2, more frequently of 3 (10 times, 40%) to the left. Thus, others deriving branches of popliteo lympho nodes right and that if they insert in the above-mentioned vein are in number of 2 and 5 (5 times, 20%), 4 and 6 (2 times, 8%) and 8 and 9 (1 time, 4%). In spite of, to the left side it is examined in number de 2 branches (6 times, 24%), 4 (4 times, 16%), 6 (3 times, 12%) and finishing 9 and 12 branches (1 time, 4%). The size of popliteo lympho node in seropositive dogs for Visceral Leishmaniasis can meets enters 7,8 × 3,8 × 6,1 a 50,0 × 20,7 × 28,5, in mm, being average 26,18 × 10,5 × 15,97 mm for right and 26,98 × 11,14 × 15,25 mm for left (concerning the measures dorsoventral, latero-lateral and cranial-caudal, respectively).
Arterial and venous vasculature of popliteo lymph nodes in dogs
Keywords: Anatomy; Dogs; Popliteo lympho nodes; Vasculature; Animalia; Canis familiaris